Spatial Modeling for Wind Erosion Measurement Using Spectral Indicators and Evidence in Diyala Governorate - Muhssin, Majed (Al-Adab Journal, 2025)
Wind erosion modeling is one of the important topics because it affects the environment according to the information revolution and digital technologies that the world is witnessing, leaving the field in a vision that mimics reality to reveal the behavior of the effect of wind on drawing landforms, and this reflects an image in the form of a cartographic (effective map) to reveal the effect of wind on the environment in The area is considered one of the fertile areas for agricultural production, so it was important to build models of wind erosion for the area. The area of the study area was 17,617 km2. The differences in the rate of wind erosion between the years (2010-2023) in the region was measured through mathematical equations, building digital models, and using several indicators based on modern remote sensing. It became clear that the area of barren lands in the year 2010 was 6,808 km2, and in the year 2023 it increased. The area reached 8,802 km2. The wind erosion index for the year 2010 was 3,989 km2, and its area increased in 2023, reaching 5,809 km2. This difference in proportions is due to several reasons.